Anti-radiation concrete based on iron tailing waste and preparation method thereof
By using modified iron tailings and barium ferrite powder composite aggregate, the construction difficulties of radiation-proof concrete have been solved, achieving uniformity and efficient radiation shielding, and reducing waste of building space and resource consumption.
Patent Information
- Application Number
- CN202511335999.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2026-01-13
AI Technical Summary
The use of ultra-high density aggregates in existing radiation-shielding concrete makes the mixture difficult to construct, prone to segregation and uneven structure, affecting the radiation shielding effect and increasing the waste of building space.
A composite aggregate made of modified iron tailings and barium ferrite powder, combined with PCA-I type polycarboxylate superplasticizer and boron carbide powder, is used to form a stable concrete system by ball milling the iron tailings, thus avoiding aggregate settling and bleeding.
It achieves uniformity and fluidity of concrete, improves construction efficiency, reduces waste of building space, and enhances radiation shielding performance and equipment operation safety.
Smart Images

Figure SMS_6 
Figure SMS_7 
Figure SMS_8
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of concrete preparation, and particularly relates to an anti-radiation concrete based on iron tailing waste and a preparation method thereof. BACKGROUND
[0002] At present, more and more hospitals consider the construction of linear accelerators when planning and constructing. The linear accelerator releases high-energy rays in the implementation of the treatment process. Therefore, the linear accelerator must avoid the influence of high-energy rays on the surrounding environment in the process of medical treatment function. How to avoid and reduce the influence of rays on the surrounding environment is also the research direction of the construction of the linear accelerator. The shielding radiation mode usually includes room structure radiation shielding and installing radiation-proof decorative panels for radiation-proof. The structure radiation shielding structure usually adopts super-thick walls and floors to realize, such as the maximum thickness of the floor of Jining Public Health Traditional Chinese Medicine Medical Center is 3m, and the maximum thickness of the wall is 3m. In order to ensure that the linear accelerator room does not produce radiation influence on the surrounding environment in the use process, super-heavy concrete is usually used to realize the room structure radiation-proof function. The volume weight of ordinary concrete is generally about 2400kg / m3. The volume weight of the anti-radiation concrete is larger than that of the ordinary concrete, and can even reach twice that of the ordinary concrete. The anti-radiation concrete usually adopts iron ore, barite, iron sand and the like as aggregate for mixing. However, due to the large specific gravity of these coarse aggregates compared with ordinary crushed stone, the mixture is difficult to produce and construct, and is prone to coarse aggregate settlement, layering, segregation, bleeding and the like. At the same time, the high-density characteristics of the heavy aggregate cause the working property of the concrete mixture to deteriorate sharply. The coarse aggregate settles rapidly in the pouring process, causing layering and segregation and surface bleeding, forming a non-uniform internal structure. Such non-uniformity not only reduces the mechanical strength of the concrete, but also forms a radiation leakage channel in the shielding body, forcing the designer to further increase the wall thickness to compensate for the protection defects, causing waste of building space and a sharp increase in cost.
[0003] How to solve the above technical problems is the subject faced by the present application. SUMMARY
[0004] In order to solve the problems of the prior art, the present application provides an anti-radiation concrete based on iron tailing waste and a preparation method thereof by using tailing waste to produce anti-radiation concrete, which comprehensively utilizes solid waste and reduces environmental pollution.
[0005] The application solves the technical problems by adopting the technical scheme that the application provides an anti-radiation concrete based on iron tailings waste, which is made of the following raw materials in parts by weight: P·O42.5 cement 200-240 parts, I-grade fly ash 100-130 parts, S95-grade mineral powder 90-100 parts, composite aggregate 2000-2350 parts, water 150-165 parts, water reducing agent 10.5-12 parts, and boron carbide powder 1-3 parts. The composite aggregate comprises coarse aggregate and fine aggregate, and the fine aggregate is modified iron tailings sand, which is made of iron tailings sand and barium ferrite powder by ball milling coating.
[0006] The weight ratio of the coarse aggregate to the fine aggregate in the composite aggregate is 1.2-1.4:1.
[0007] The coarse aggregate is composed of iron ore with an apparent density of ≥4000 kg / m³ and iron tailings ore with an apparent density of ≥2900 kg / m³ at a weight ratio of 1:0.8-1.2.
[0008] The dosage of the barium ferrite powder in the modified iron tailings sand is 8-12% of the weight of the iron tailings sand.
[0009] The barium ferrite powder has a particle size of ≤50 μm.
[0010] The water reducing agent is PCA-I type polycarboxylic acid water reducing agent. The boron carbide powder has a particle size of 1-10 μm and a purity of ≥98%.
[0011] A preparation method of an anti-radiation concrete based on iron tailings waste, comprising the following preparation steps: S1, mixing iron tailings sand and barium ferrite powder at a weight ratio of 100:8-12 and ball milling for 30 minutes; S2, dry mixing P·O42.5 cement, I-grade fly ash, S95-grade mineral powder, and boron carbide powder for 40-60 seconds; S3, adding water and water reducing agent to the product obtained in step S2 and stirring for 90 seconds to form a slurry; S4, adding coarse aggregate and fine aggregate obtained in step S1 to the slurry in step S3, and discharging after stirring for 180 seconds; S5, injecting the obtained concrete into a mold and applying a vibration pressure of 0.5-1.0 MPa at a frequency of 50-100 Hz for 3-5 minutes.
[0012] The specific surface area of the modified iron tailings sand after ball milling in step S1 is 450-500 m² / kg.
[0013] The MB value of the modified iron tailings sand is ≤1.0, and the 28d heavy metal leaching concentration is ≤0.1 mg / L.
[0014] The beneficial effects of this invention are as follows: 1. Traditional radiation-shielding concrete uses ultra-high density aggregates, which inevitably lead to aggregate settlement and slurry separation during mixing and pouring, severely restricting construction quality and efficiency. This solution uses iron tailings aggregate modification technology to significantly eliminate segregation and bleeding while maintaining the ultra-high density characteristics of concrete. The modified aggregates and cement slurry form a highly stable and homogeneous system, achieving excellent fluidity, allowing the concrete to be pumped smoothly and complete large-volume continuous pouring. This not only greatly improves construction efficiency but also eliminates the weakness in shielding performance caused by material stratification from the source, providing a reliable guarantee for radiation protection structures.
[0015] 2. Traditional concrete systems, in order to compensate for the non-uniformity of materials, have to adopt ultra-thick wall structures, resulting in wasted medical building space and excessive consumption of resources. The high uniformity of materials achieved in this solution enables concrete to reach a new level of radiation shielding performance. Under the premise of meeting the same protection standards, the wall thickness is significantly reduced, freeing up valuable treatment space for medical institutions. At the same time, the density and homogeneity of the overall concrete structure can ensure stable and reliable radiation attenuation effect, avoid the risk of radiation leakage, and improve the operational safety of medical equipment such as linear accelerators to a new level.
[0016] 3. This solution breaks through the dependence of traditional radiation-proof concrete on scarce mineral resources and innovatively transforms iron tailings solid waste into high-performance aggregates. This technical approach not only effectively disposes of mountains of industrial waste, but also significantly reduces the demand for natural ore mining, reflecting the dual value of resource conservation and environmental friendliness. This technology sets a new green and low-carbon benchmark for radiation protection engineering in medical buildings, promotes the transformation of the engineering construction field towards a circular economy model, and achieves the organic unity of ecological benefits and economic and social benefits. Detailed Implementation
[0017] To clearly illustrate the technical features of this solution, the following detailed implementation method will be used to explain the solution.
[0018] Example 1 This embodiment is a radiation-resistant concrete based on iron tailings waste, which is made from the following raw materials in parts by weight: 220 parts of P·O42.5 cement, 115 parts of Grade I fly ash, 95 parts of S95 grade mineral powder, 2250 parts of composite aggregate, 158 parts of water, 11.2 parts of PCA-I type polycarboxylate superplasticizer, and 2 parts of boron carbide powder. The composite aggregate includes coarse aggregate and fine aggregate. The fine aggregate is modified iron tailings, which is made by ball milling and coating iron tailings and barium ferrite powder. The weight ratio of coarse aggregate to fine aggregate in the composite aggregate is 1.3:1, including 1275 parts of coarse aggregate and 975 parts of fine aggregate. The coarse aggregate is composed of iron ore with an apparent density of 4100 kg / m³ and iron tailings with an apparent density of 3010 g / m³ in a weight ratio of 1:1, with 637.5 parts of each.
[0019] The modified iron tailings contained 885 parts iron tailings and 88.5 parts barium ferrite powder. The barium ferrite powder was... The particle size is 45 μm. The boron carbide powder has a particle size of 5 μm and a purity of 99%.
[0020] A method for preparing radiation-resistant concrete based on iron tailings waste includes the following preparation steps: S1. Mix iron tailings and barium ferrite powder and ball mill for 30 minutes. The specific surface area of the modified iron tailings after ball milling is 480 m² / kg, the MB value of the modified iron tailings is 0.8, and the heavy metal leaching concentration after 28 days is 0.05 mg / L. S2. Dry mix P·O42.5 cement, Grade I fly ash, S95 grade mineral powder, and boron carbide powder for 50 seconds. S3. Add water and water-reducing agent to the product obtained in step S2 and stir at 300 rpm for 90 seconds to form a slurry. S4. Add coarse aggregate and fine aggregate obtained in step S1 to the slurry in step S3. The coarse aggregate and modified fine aggregate are added in two batches: the first batch of 60% aggregate is mixed with the slurry for 60 seconds, and then the remaining 40% aggregate is added and mixed for 120 seconds. After a total of 180 seconds of mixing, the material is discharged. S5. After the obtained concrete is injected into the mold, apply a vibration pressure of 0.8MPa at a frequency of 80Hz for 4 minutes.
[0021] Example 2 This embodiment is a radiation-resistant concrete based on iron tailings waste, which is made from the following raw materials in parts by weight: 210 parts of P·O42.5 cement, 120 parts of Grade I fly ash, 95 parts of S95 grade mineral powder, 2250 parts of composite aggregate, 158 parts of water, 11.2 parts of PCA-I type polycarboxylate superplasticizer, and 2 parts of boron carbide powder. The composite aggregate includes coarse aggregate and fine aggregate. The fine aggregate is modified iron tailings, which is made by ball milling and coating iron tailings and barium ferrite powder. The weight ratio of coarse aggregate to fine aggregate in the composite aggregate is 1.3:1, including 1275 parts of coarse aggregate and 975 parts of fine aggregate. The coarse aggregate is composed of iron ore with an apparent density of 4100 kg / m³ and iron tailings with an apparent density of 3010 g / m³ in a weight ratio of 1:1, with 637.5 parts of each.
[0022] The modified iron tailings contained 885 parts iron tailings and 90 parts barium ferrite powder. The barium ferrite powder was... The particle size is 45 μm. The boron carbide powder has a particle size of 5 μm and a purity of 99%.
[0023] A method for preparing radiation-resistant concrete based on iron tailings waste includes the following preparation steps: S1. Mix iron tailings and barium ferrite powder and ball mill for 30 minutes. The specific surface area of the modified iron tailings after ball milling is 480 m² / kg, the MB value of the modified iron tailings is 0.8, and the heavy metal leaching concentration after 28 days is 0.05 mg / L. S2. Dry mix P·O42.5 cement, Grade I fly ash, S95 grade mineral powder, and boron carbide powder for 50 seconds. S3. Add water and water-reducing agent to the product obtained in step S2 and stir at 300 rpm for 90 seconds to form a slurry. S4. Add coarse aggregate and fine aggregate obtained in step S1 to the slurry in step S3. The coarse aggregate and modified fine aggregate are added in two batches: the first batch of 60% aggregate is mixed with the slurry for 60 seconds, and then the remaining 40% aggregate is added and mixed for 120 seconds. After a total of 180 seconds of mixing, the material is discharged. S5. After the obtained concrete is injected into the mold, apply a vibration pressure of 0.8MPa at a frequency of 80Hz for 4 minutes.
[0024] Example 3 This embodiment is a radiation-resistant concrete based on iron tailings waste, which is made from the following raw materials in parts by weight: 220 parts of P·O42.5 cement, 115 parts of Grade I fly ash, 95 parts of S95 grade mineral powder, 2250 parts of composite aggregate, 158 parts of water, 11.2 parts of PCA-I type polycarboxylate superplasticizer, and 2 parts of boron carbide powder. The composite aggregate includes coarse aggregate and fine aggregate. The fine aggregate is modified iron tailings, which is made by ball milling and coating iron tailings and barium ferrite powder. The weight ratio of coarse aggregate to fine aggregate in the composite aggregate is 1.3:1, including 1300 parts of coarse aggregate and 1000 parts of fine aggregate. The coarse aggregate is composed of iron ore with an apparent density of 4100 kg / m³ and iron tailings with an apparent density of 3010 g / m³ in a weight ratio of 1:1, with 650 parts of each.
[0025] The modified iron tailings consist of 910 parts iron tailings and 90 parts barium ferrite powder. The barium ferrite powder is... The particle size is 45 μm. The boron carbide powder has a particle size of 5 μm and a purity of 99%.
[0026] A method for preparing radiation-resistant concrete based on iron tailings waste includes the following preparation steps: S1. Mix iron tailings and barium ferrite powder and ball mill for 30 minutes. The specific surface area of the modified iron tailings after ball milling is 480 m² / kg, the MB value of the modified iron tailings is 0.8, and the heavy metal leaching concentration after 28 days is 0.05 mg / L. S2. Dry mix P·O42.5 cement, Grade I fly ash, S95 grade mineral powder, and boron carbide powder for 50 seconds. S3. Add water and water-reducing agent to the product obtained in step S2 and stir at 300 rpm for 90 seconds to form a slurry. S4. Add coarse aggregate and fine aggregate obtained in step S1 to the slurry in step S3. The coarse aggregate and modified fine aggregate are added in two batches: the first batch of 60% aggregate is mixed with the slurry for 60 seconds, and then the remaining 40% aggregate is added and mixed for 120 seconds. After a total of 180 seconds of mixing, the material is discharged. S5. After the obtained concrete is injected into the mold, apply a vibration pressure of 0.8MPa at a frequency of 80Hz for 4 minutes.
[0027] Example 4 This embodiment is a radiation-resistant concrete based on iron tailings waste, which is made from the following raw materials in parts by weight: 220 parts of P·O42.5 cement, 115 parts of Grade I fly ash, 95 parts of S95 grade mineral powder, 2250 parts of composite aggregate, 158 parts of water, 11.2 parts of PCA-I type polycarboxylate superplasticizer, and 1.5 parts of boron carbide powder. The composite aggregate includes coarse aggregate and fine aggregate. The fine aggregate is modified iron tailings, which is made by ball milling and coating iron tailings and barium ferrite powder. The weight ratio of coarse aggregate to fine aggregate in the composite aggregate is 1.3:1, including 1275 parts of coarse aggregate and 975 parts of fine aggregate. The coarse aggregate is composed of iron ore with an apparent density of 4100 kg / m³ and iron tailings with an apparent density of 3010 g / m³ in a weight ratio of 1:1, with 637.5 parts of each.
[0028] The modified iron tailings contained 878 parts iron tailings and 97 parts barium ferrite powder. The barium ferrite powder was... The particle size is 45 μm. The boron carbide powder has a particle size of 5 μm and a purity of 99%.
[0029] A method for preparing radiation-resistant concrete based on iron tailings waste includes the following preparation steps: S1. Mix iron tailings and barium ferrite powder and ball mill for 30 minutes. The specific surface area of the modified iron tailings after ball milling is 480 m² / kg, the MB value of the modified iron tailings is 0.8, and the heavy metal leaching concentration after 28 days is 0.04 mg / L. S2. Dry mix P·O42.5 cement, Grade I fly ash, S95 grade mineral powder, and boron carbide powder for 50 seconds. S3. Add water and water-reducing agent to the product obtained in step S2 and stir at 300 rpm for 90 seconds to form a slurry. S4. Add coarse aggregate and fine aggregate obtained in step S1 to the slurry in step S3. The coarse aggregate and modified fine aggregate are added in two batches: the first batch of 60% aggregate is mixed with the slurry for 60 seconds, and then the remaining 40% aggregate is added and mixed for 120 seconds. After a total of 180 seconds of mixing, the material is discharged. S5. After the obtained concrete is injected into the mold, apply a vibration pressure of 0.8MPa at a frequency of 80Hz for 4 minutes.
[0030] Comparative Example 1 The radiation-proof concrete formula used in the linear accelerator room of a tertiary hospital was adopted: 220 parts of P·O42.5 cement, 60 parts of Class I fly ash, 80 parts of S95 mineral powder, 1250 parts of iron ore aggregate (apparent density 4100kg / m³), 950 parts of barite aggregate (apparent density 4300kg / m³), 160 parts of water, and 10 parts of naphthalene-based water-reducing agent.
[0031] Prepare each group of concrete according to the proportions in Table 1, and measure the following indicators for each group of concrete: dry density, measured concrete strength, crack resistance, slump, etc.
[0032] Table 1. Reference table of concrete mix proportions for each experimental group
[0033] 1. Slump test The slump test was conducted according to GB / T 50080-2016 Standard for Test Methods of Performance of Concrete Mixtures for Building Construction: A wetted slump cone, 300mm high, 200mm in diameter at the bottom, and 100mm in diameter at the top, was placed on a flat, wetted steel plate. Fresh concrete from Examples 1-4 and the comparative proportions was added in three layers, with each layer tamped 25 times. After leveling the top surface, the cone was slowly and vertically lifted, and the vertical height from the highest point of concrete slump to the top of the cone was measured. Simultaneously, the cohesiveness and water retention of the mixture were observed. The entire process was completed within 5-15 seconds at an ambient temperature of 20±5℃. The test results are shown in Table 4.
[0034] Table 2. Concrete slump test results for each group
[0035] Tests showed that all embodiments had a slump of 195-210 mm and good water retention, with an expansion of over 470 mm, confirming that the new formulation formed a stable slurry coating layer under the action of fly ash and synergistic water-reducing agent. The comparative embodiment, on the other hand, showed water bleeding due to the lack of micro-aggregate lubrication effect, and the expansion was less than 420 mm.
[0036] 2. Dry density determination By measuring the initial weight and dry density of concrete in each test group, the weight loss of each test group was obtained. The average weight loss of each test group was taken to obtain the relationship between the initial weight and the dry density. Thus, the initial weight corresponding to a dry density of 2800 kg / m3 can be determined when using local materials.
[0037] Table 3 Results of concrete dry density tests for each group
[0038] As can be seen from the dry density results in Table 3, the weight loss of the example group after drying for 120 hours was only 86-90g, with a loss rate of <3.1%, which is significantly lower than the 3.6% of the comparative example. This proves that the optimization of the iron-based aggregate gradation effectively improves the density and lays the structural foundation for radiation protection performance.
[0039] 3. Radiation attenuation test Three 100mm cubic specimens (cured to constant weight after 60 days of standard curing) were stacked to form a 300mm×100mm×100mm shield using dry density test specimens. The surface was wrapped with aluminum foil to eliminate the influence of pore scattering. The penetration count rate of the radioactive source (0.662 MeV) at a source distance of 50 cm was measured using a NaI(Tl) energy dispersive spectrometer, and the linear attenuation coefficient μ = 1 / t·ln( The shielding efficiency was calculated using the ( / N) and a 30cm thickness. The results are shown in Table 4.
[0040] Table 4 Results of X-ray attenuation tests for each group
[0041] Example 4, containing 97 kg / m³ barium iron hydrogen, exhibits a linear decay coefficient of 0.198 cm⁻¹. The comparison ratio is 43% higher, and the shielding rate of 30cm thickness exceeds 99.8%, highlighting the characteristic absorption advantage of barium for gamma rays.
[0042] 4. Strength Measurement Cement content is an indicator affecting concrete strength. When the cement content decreases, the concrete strength will gradually decrease. Therefore, during the concrete mixing process in this experiment, the concrete strength needs to be continuously tested. Due to the large amount of fly ash added to the concrete, the concrete reaches its design strength relatively slowly. Therefore, during the mixing process, the 7-day, 28-day, and 60-day strengths of the concrete were continuously tested. The concrete strength test was strictly carried out in accordance with the "GB / T 50081-2016 Standard for Test Methods of Physical and Mechanical Properties of Concrete": 100mm*100mm*100mm cube specimens were placed in a standard curing room and cured to the specified age (7d / 28d / 60d) at a temperature of 20±2℃ and a relative humidity of ≥95%. A pressure testing machine was used to apply pressure uniformly along the direction perpendicular to the pouring surface at a loading rate of 0.8MPa / s. The maximum load value at the time of specimen failure was recorded. After correction by a size conversion factor of 0.95, the representative value of the compressive strength at that age (accurate to 0.1MPa) was obtained. The test results are shown in Table 3.
[0043] Table 5. Concrete strength test results for each group
[0044] The 60-day strength of all example groups exceeded 44.9 MPa, an increase of >8.5% compared to 28 days, with Example 1 reaching 45.8 MPa. In contrast, the comparative example, due to a 23% reduction in the total amount of adhesive material, had a 60-day strength of only 33.1 MPa, highlighting the beneficial effect of mineral admixtures on long-term performance.
[0045] The technical features of this invention not described can be implemented by or using existing technology, and will not be repeated here. Of course, the above description is not a limitation of this invention, and this invention is not limited to the examples above. Any changes, modifications, additions or substitutions made by those skilled in the art within the scope of this invention should also be within the protection scope of this invention.
Claims
1. A radiation-resistant concrete based on iron tailings waste, characterized in that, It is made from the following raw materials in parts by weight: 200-240 parts of P·O42.5 cement, 100-130 parts of Grade I fly ash, 90-100 parts of S95 grade mineral powder, 2000-2350 parts of composite aggregate, 150-165 parts of water, 10.5-12 parts of water-reducing agent, and 1-3 parts of boron carbide powder; The composite aggregate includes coarse aggregate and fine aggregate. The fine aggregate is modified iron tailings, which is made by ball milling and coating iron tailings with barium ferrite powder.
2. The radiation-resistant concrete based on iron tailings waste according to claim 1, characterized in that, The weight ratio of coarse aggregate to fine aggregate in the composite aggregate is 1.2-1.4:
1.
3. The radiation-resistant concrete based on iron tailings waste according to claim 1, characterized in that, The coarse aggregate is composed of iron ore with an apparent density ≥ 4000 kg / m³ and iron tailings with an apparent density ≥ 2900 kg / m³ in a weight ratio of 1:0.8-1.
2.
4. The radiation-resistant concrete based on iron tailings waste according to claim 1, characterized in that, The amount of barium ferrite powder in the modified iron tailings is 8-12% of the weight of the iron tailings.
5. The radiation-resistant concrete based on iron tailings waste according to claim 1, characterized in that, The barium ferrite powder is Particle size ≤ 50 μm.
6. The radiation-resistant concrete based on iron tailings waste according to claim 1, characterized in that, The water-reducing agent is PCA-I type polycarboxylate water-reducing agent.
7. The radiation-resistant concrete based on iron tailings waste according to claim 1, characterized in that, The boron carbide powder has a particle size of 1-10 μm and a purity of ≥98%.
8. A method for preparing radiation-resistant concrete based on iron tailings waste as described in any one of claims 1-7, characterized in that, The preparation steps include the following: S1. Mix iron tailings and barium ferrite powder at a weight ratio of 100:8-12 and ball mill for 30 minutes. S2. Dry mix P·O42.5 cement, Grade I fly ash, S95 grade mineral powder, and boron carbide powder for 40-60 seconds. S3. Add water and water-reducing agent to the product obtained in step S2 and stir for 90 seconds to form a slurry; S4. Add coarse aggregate and fine aggregate obtained in step S1 to the slurry in step S3, stir for 180 seconds and then discharge. S5. After the obtained concrete is poured into the mold, apply a vibration pressure of 0.5-1.0MPa at a frequency of 50-100Hz for 3-5 minutes.
9. The method for preparing radiation-resistant concrete based on iron tailings waste according to claim 8, characterized in that, The specific surface area of the modified iron tailings after ball milling in step S1 is 450-500 m² / kg.
10. The method for preparing radiation-resistant concrete based on iron tailings waste according to claim 8, characterized in that, The modified iron tailings has an MB value ≤ 1.0 and a 28-day heavy metal leaching concentration ≤ 0.1 mg / L.